Differential cellular immune response of hemocyte of Galleria mellonella larvae against Actinobacillus pleuropneumoniae strains - Arteaga Blanco, Luis Andres (2016)
Insects respond to infection by mounting cellular and humoral immune reactions. The primary regulators of these immune responses are cells called hemocytes, which mediate important cellular immune responses including phagocytosis, encapsulation, nodulation and also secrete immune factors such as opsonins, melanization factors and antimicrobial peptides. Hemocytes circulate through the hemocoel (body cavity) by the swift flow of hemolymph (blood), and part of these hemocytes population are sessile and are attached to tissues. Larvae of Galleria mellonella is a widely used factitious host as a viable alternative to traditional mammalian models to study the efficacy of antimicrobial drugs and the microbial pathogenesis in vivo. However, despite their importance as an infection model, biological aspects about the immune cells, such as density and hemocyte dynamic of larvae are poorly understood. In the present study, we investigated the cellular immune response of hemocytes from G. mellonella larvae against three strains of the gram-negative bacterium Actinobacillus pleuropneumoniae: low virulent (780), high virulent (1022), and the serotype 8 reference strain (R8). Five types of larval hemocytes, prohemocytes, plasmatocytes, granulocytes, oenocytoids, and spherulocytes, were distinguished according to size, morphology, detection by molecular probes, dye-staining properties, and their role in the immune response. Total hemocyte count, differential hemocyte count, lysosome activity, autophagic response, cell viability, and caspase-3 activation were determined in circulating hemocytes of naïve and infected larvae. Granulocytes and plasmatocytes were the major hemocyte types involved in the cellular defense against A. pleuropneumoniae; these hemocytes activated phagolysosome activities associated with an autophagic response against the bacteria. Moreover, our results showed that apoptosis in circulating hemocytes after exposure to virulent bacterial strains was related to an excessive autophagic cell death response induced by stress and subsequent caspase-3 activation.